COMPUTATIONAL FLUID DYNAMICS INVESTIGATION ON THE USE OF PHASE CHANGE MATERIAL (PCM) HEAT EXCHANGER TO PROVIDE COOLING FOR BUILDING THERMAL COMFORT - RAM NAIR, SAYSHAR (2018)
Buildings use HVACs which stand for Heating, Ventilation and Air-Conditioning that is known to consume a significant amount of power to run. As space cooling demand rises, so does the need for more economical and environmentally-friendly options to be explored. The use of PCMs for thermal energy storage is not a new topic and has been an ongoing research area for many years. Based on existing research, PCMs can be used within HVACs to reduce the electrical load needed to provide air cooling as well as be incorporated into the walls of the building to ensure a cooler indoor space without a full load on the HVAC during the day. The novelty of this research is to investigate the potential energy savings by incorporating PCM into the walls of the building as well as within the heat exchanger which supplies air to the building. This report shows the meshed models of both the PCM containing heat exchanger and that of the building that is being simulated. The report also contains the temperature data obtained from the heat exchanger which will be used as the inlet condition for the modelled building. The results will then be compared with a non PCM containing building to quantify the potential energy saving that can be achieved by having PCM within the walls of the building.